Analysis of High Body Mass Index (BMI) and Workplace Fatigue as Risk Factors for Needle Stick Injury Incidents Nurse at Bali Mandara Regional General Hospital - Maheri, Ni Luh Maya; Duana, Made Kerta; Suarjana, Ketut (Babali Publisher, 2026)
Background: Hospital environments pose a high risk of occupational accidents, with needle stick injuries (NSIs) being among the most prevalent, especially among nursing staff. At Bali Mandara Regional General Hospital, 47 NSI cases were reported between January 2022 and July 2025, highlighting a serious occupational health concern. Objective: This study aims to analyze the correlation between Body Mass Index (BMI) and workplace fatigue as risk factors for Needle Stick Injury (NSI) incidents among nurses at Bali Mandara Regional General Hospital. Methods: An analytical observational study with a cross-sectional design was conducted in February 2026. A sample of 199 nurses was selected using simple random sampling. Data were collected through questionnaires covering respondent characteristics, BMI measurements, and the Fatigue Assessment Scale (FAS). Data analysis involved Chi-square tests for bivariate analysis and logistic regression for multivariate analysis. Results: The study found that 17.1% of respondents had experienced an NSI. Statistical analysis showed no significant correlation between BMI and NSI incidents (p = 0.695). However, a significant correlation was found between workplace fatigue and NSI incidents (p < 0.001). Nurses experiencing fatigue were 7.17 times more likely to suffer from an NSI compared to those without fatigue (OR = 7.17; 95% CI = 2.817–18.295). Conclusion: Workplace fatigue is a significant risk factor for needle stick injuries among nurses at Bali Mandara Regional General Hospital, whereas BMI does not show a significant impact. Management should prioritize fatigue mitigation strategies and occupational safety training to reduce the prevalence of NSI.